2019
DOI: 10.1038/s41598-019-47551-4
|View full text |Cite|
|
Sign up to set email alerts
|

The population structure of Clostridium tetani deduced from its pan-genome

Abstract: Clostridium tetani produces a potent neurotoxin, the tetanus neurotoxin (TeNT) that is responsible for the worldwide neurological disease tetanus, but which can be efficiently prevented by vaccination with tetanus toxoid. Until now only one type of TeNT has been characterized and very little information exists about the heterogeneity among C . tetani strains. We report here the genome sequences of 26 C . tetani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…One serotype of TeNT is known, whilst eight different serotypes of BoNT have been characterized (BoNT/A, /B, /C, /D, /E, /F, /G, and /X) [2,8]. TeNT proteins with little variation in amino acid sequence, that do not alter significantly their antigenicity, have been recently reported [9,10], whereas many dozens of BoNTs with very variable primary structures and ensuing different biological properties and antigenicity have been described. They are defined as subtypes of a given serotype and indicated with arabic numbers (for example BoNT/A1, BoNT/A2, etc.)…”
Section: Clostridial Neurotoxinsmentioning
confidence: 99%
“…One serotype of TeNT is known, whilst eight different serotypes of BoNT have been characterized (BoNT/A, /B, /C, /D, /E, /F, /G, and /X) [2,8]. TeNT proteins with little variation in amino acid sequence, that do not alter significantly their antigenicity, have been recently reported [9,10], whereas many dozens of BoNTs with very variable primary structures and ensuing different biological properties and antigenicity have been described. They are defined as subtypes of a given serotype and indicated with arabic numbers (for example BoNT/A1, BoNT/A2, etc.)…”
Section: Clostridial Neurotoxinsmentioning
confidence: 99%
“…The 114 nt sequence of the putative sRNA was identified also in all other plasmid-positive Harvard-derived strains clade 1A strains, according to 22 , such as E88, CN655, and strain A with a 100% identity on nucleotide level. In addition, all plasmid-positive C. tetani strains of clades 1B to 1E carry an identical sequence (with strain TMB2, a clade 1B strain, as the only exception) (Sup.…”
Section: Resultsmentioning
confidence: 88%
“…S2 ). We took advantage of the strain 1586-Z1, which is a non-toxigenic derivative of the clade 1A strain 1586-U1 22 . Both strains, 1586-Z1 and 1586-U1, retain the same chromosomal genome sequence, but 1586-Z1 lacks the wild-type large plasmid harboring tent 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome contains a chromosome of approximately 2.8 Mb and a TeNT-encoding plasmid of 74 kb. The genomes of additional C. tetani strains have been sequenced and showed that the plasmid-encoded tent is highly conserved [10][11][12]. A conserved gene (tetR, tetanus toxin regulatory gene) just upstream of tent encodes for an alternative sigma factor which positively regulates the transcription of tent [13].…”
Section: Introductionmentioning
confidence: 99%